DISTINCTIVE FEATURES OF CHINA’S STRATEGY IN SHAPING REGIONAL AND GLOBAL SECURITY ARCHITECTURES - Sadibakosev , Khabibullo (QO‘QON UNIVERSITETI XABARNOMASI, 2026)
China’s approach to the formation of regional and global security systems represents a complex combination of soft power instruments, economic interdependence, and strategic diplomacy aimed at ensuring a secure environment for national development while contributing to global stability. Rooted in Confucian philosophical traditions, China’s security thinking prioritizes harmony, stability, and the minimization of conflict. Economically, China capitalizes on its position as a leading trading partner for numerous states, using economic connectivity as a tool for fostering cooperation and influence, most notably through large-scale initiatives such as the Belt and Road Initiative. At the diplomatic level, China promotes a vision of multilateral global governance and advocates reforming international institutions to better reflect the pluralistic and interconnected nature of the contemporary international system. This approach often contrasts with Western security paradigms, which traditionally emphasize military alliances and interventionist practices. Regionally, China seeks to maintain stable relations with neighboring states through mechanisms such as the Shanghai Cooperation Organization and active engagement in ASEAN-led forums. Nevertheless, China’s growing influence is accompanied by persistent challenges, including territorial disputes, regional tensions, and concerns related to the expansion of its military capabilities.